please give me the reason and solution of this question
Attachments:
![](https://hi-static.z-dn.net/files/d49/d4a4567f2170498ba7e7797adfb8ba11.jpg)
Answers
Answered by
0
when roots are given then we can frame the eqns by
x-a)(x-b)=0
here two roots are there so we will get a quadratic eqn by putting a=-2and b=5
(x+2)(x-5)=0
x-a)(x-b)=0
here two roots are there so we will get a quadratic eqn by putting a=-2and b=5
(x+2)(x-5)=0
Similar questions
English,
8 months ago
Science,
8 months ago
Geography,
1 year ago
Social Sciences,
1 year ago
History,
1 year ago